Komunikasi Partisipatoris Program Kotaku Dalam Mengurangi Kawasan Kumuh di Kampung Ketupat Samarinda Sebrang - Sugandi Sugandi; Kheyene Molekandella Boer; Johantan Alfando (Universitas Muhammadiyah Sidoarjo, 2020)
The City without Slums Program (KotaKu) in Samarinda Sebrang Ketupat Village has been running for one year. Weaving villages are classified as slums. The general objective of this program is to increase access to infrastructure and basic services in urban slums to support the realization of habitable, productive and sustainable urban settlements. The research method uses qualitative with in-depth interview techniques with key informants and informants and observations. The results of the study pursed on three concepts of the approach used by the KotaKu team in communicating messages to the people of the weaving village; monologic communication, dialogic communication and multitract communication. The collaboration of these three participatory communication approaches is an effective way to change people's behavior and paradigms to change their lifestyle, habits become healthier and cleaner. The suggestion for this research is that the government should carry out continuous monitoring to see the condition after the weaving village is improved.